Contactin-associated protein-2 antibodies in non-paraneoplastic cerebellar ataxia. Issue 4 (15th February 2012) - Becker, Esther B E; Zuliani, Luigi; Pettingill, Rosemary; Lang, Bethan; Waters, Patrick; Dulneva, Anna; Sobott, Frank; Wardle, Mark; Graus, Francesc; Bataller, Luis; Robertson, Neil P; Vincent, Angela
Abstract : Background: Relatively few studies have searched for potentially pathogenic antibodies in non-paraneoplastic patients with cerebellar ataxia. Methods and Results: We first screened sera from 52 idiopathic ataxia patients for binding of serum IgG antibodies to cerebellar neurons. One strong-binding serum was selected for immunoprecipitation and mass spectrometry, which resulted in the identification of contactin-associated protein 2 (CASPR2) as a major antigen. CASPR2 antibodies were then found by a cell-based assay in 9/88 (10%) ataxia patients, compared to 3/144 (2%) multiple sclerosis or dementia controls (p=0.011). CASPR2 is strongly expressed in the cerebellum, only partly in association with voltage-gated potassium channels. Conclusions: Prospective studies are now needed to see whether identification of CASPR2 antibodies has relevance for the diagnosis and treatment of idiopathic cerebellar ataxia.